1968
DOI: 10.1252/jcej.1.153
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Suspended Solid Particles in the Bubble Column

Abstract: The behavior of suspended solid particles in the bubble column was experimentally studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 1 publication
2
40
0
Order By: Relevance
“…Studies in FAL bubble columns, [13] however, showed that critical air velocity increased with tank diameter. This observation is in conformity with Imafuku et al [9] and Smith et al, [14] but is opposite to that reported by Hallett et al, [6] Roy et al, [8] and Furchner and Mersmann. [12] Bubble columns differ from Pachuca tanks (Table I) both in terms of dimensions and mode of operation.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Studies in FAL bubble columns, [13] however, showed that critical air velocity increased with tank diameter. This observation is in conformity with Imafuku et al [9] and Smith et al, [14] but is opposite to that reported by Hallett et al, [6] Roy et al, [8] and Furchner and Mersmann. [12] Bubble columns differ from Pachuca tanks (Table I) both in terms of dimensions and mode of operation.…”
Section: Introductionsupporting
confidence: 84%
“…Perhaps the most rigorous investigation of particle suspension in bubble columns is by Koide et al [7] They observed that the critical air velocity for off-bottom suspension was lower in tanks with a conical bottom, which was also reported by Imafuku et al [9] The FCC configuration was found to be more efficient in suspending particles than the FAL configuration. Experimental observations revealed that the critical gas velocity was at a minimum at a D d /D t ratio of 0.6.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations